Bacteriological Profile of Neonatal Sepsis in a Neonatal Intensive Care Unit of a Tertiary Care Hospital of Eastern Nepal - Yadav, Sunil Kumar; Giri, Arun (Journal of College of Medical Sciences-Nepal, 2019)
Background: Neonatal sepsis is a common and serious problem of neonates who are admitted for intensive care. It is a leading cause of neonatal morbidity and mortality worldwide. The objective of the study was to detect the common causative microorganisms of neonatal sepsis and their antibiotic susceptibility patterns in NICU of Nobel Medical College Teaching Hospital (NMCTH). Methods: This was a cross-sectional study conducted in a 17- bedded teaching and referral NICU of NMCTH from March to August, 2018. All neonates of clinical sepsis were enrolled in the study, blood cultures taken and were followed up till final outcome, which was discharge or death, irrespective of culture report. Descriptive statistics including percentages and frequencies was used.complications. Results: Among the 55 neonates with diagnosis of clinical sepsis, 13(23.6%) had shown bacteria in the culture. The predominant organisms were Staphylococcus aureus and Klebsiella pneumoniae and most of them were resistant to Ampicillin and Amikacin. Conclusions: The culture positivity rate among the neonates with clinical sepsis in the study was 23.6%. Pathogens isolated were resistant to the first line drugs for management of neonatal sepsis. Hence, the need for a review of first line drug for empirical treatment of neonatal sepsis.